Everything, everything - Yoon, Nicola 1972- (Delacorte Press, 2015)
"The story of a teenage girl who's literally allergic to the outside world. When a new family moves in next door, she begins a complicated romance that challenges everything she's ever known. The narrative unfolds via vignettes, diary entries, texts, charts, lists, illustrations, and more"...
"A novel"...Jacket cover
Keywords: Friendship; Love; Allergy; Racially mixed people; Quarantäne; Ausreißerin; Immunkrankheit; Erste Liebe; Weibliche Heranwachsende; Jugendbuch